2021
DOI: 10.3390/nano11051317
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Geometrical Shape on the Characteristics of the Multiple InN/InxGa1−xN Quantum Dot Solar Cells

Abstract: Solar cells that are based on the implementation of quantum dots in the intrinsic region, so-called intermediate band solar cells (IBSCs), are among the most widely used concepts nowadays for achieving high solar conversion efficiency. The principal characteristics of such solar cells relate to their ability to absorb low energy photons to excite electrons through the intermediate band, allowing for conversion efficiency exceeding the limit of Shockley–Queisser. IBSCs are generating considerable interest in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Let us recall that in our last study published recently [44], we developed an analytical calculation of efficiency in three types of QD shapes (cubic, spherical and cylindrical); we demonstrated that the efficiency is not very sensitive to the geometrical shape. Therefore, and for simplicity, we only analyze the case of cubic QDs.…”
Section: Electronic Propertiesmentioning
confidence: 85%
“…Let us recall that in our last study published recently [44], we developed an analytical calculation of efficiency in three types of QD shapes (cubic, spherical and cylindrical); we demonstrated that the efficiency is not very sensitive to the geometrical shape. Therefore, and for simplicity, we only analyze the case of cubic QDs.…”
Section: Electronic Propertiesmentioning
confidence: 85%
“…They have unique electronic properties, which can be tuned during manufacturing by simply changing the dot shape and size 19 . A quantum dot solar cell is obtained by incorporating quantum dots into the absorbing photovoltaic material 20 . Using a well‐tuned solar cell, it is possible to absorb a wide range of the solar spectrum, which is typically difficult to achieve by conventional solar cells, and thus the efficiency of the solar cell is eventually enhanced 21 .…”
Section: Quantum Dot Solar Cellsmentioning
confidence: 99%
“…It should be noted that conventional solar cells were made of crystalline silicon and were able to attain an efficiency of up to 26%, which led to a long time of the return of investment. However, by using quantum dot solar cells with an optimized design, it is possible to achieve much higher efficiencies, 20 which makes it possible to successfully satisfy the stakeholder requirements. For instance, the time of return of investment for conventional solar cells is around 7–10 years in the United States.…”
Section: System Analysismentioning
confidence: 99%
“…Recent advances in nano-fabrication technology have offered a wide range of opportunities for realizing quantum dots QD with various kind of shapes and confining potentials, which have attracted considerable attention due to their unique optical properties like broad absorption, tunable and narrow emission [1], as well as their potential applications in electronics and optoelectronic devices, such as solar cells [2,3], lasers [4,5], photodetectors [6], light emitting diodes (LEDs) [7] and bioimaging [8]. Today, multiple layered QDs are attracting widespread interest in modern materials science and technology, with far more advantages and tuning capabilities compared with a single QD material.…”
Section: Introductionmentioning
confidence: 99%
“…The study in Ref. [2] indicates that, by changing the shape of quantum dots, the performance of solar cells is slightly modified. Moreover, it has been demonstrated that the quantum dots size, and light concentration play a key role in searching the maximum efficiency of multiple quantum dot solar cells.…”
Section: Introductionmentioning
confidence: 99%